Assessing the attitudes and perceptions of councillors and officials on integrated development planning : a case study-the Municipality of Stellenbosch - Ceasar, Niklaas (Stellenbosch : Stellenbosch University, 2012)
Thesis (MPA)--University of Stellenbosch, 1999.